Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Asli Daerah (PAD) Sub Sektor Pariwisata Di Kabupaten Lombok Utara Tahun 2015-2022 - M. Gadafi (Kredibel: Jurnal Ilmiah Manajemen, 2024)
This research aims to analyze the influence of the Number of Tourist Attractions (X1), Number of Tourists(X2 ), Number of Hotels (X3) and Number of Restaurants (X4) partially and simultaneously on local revenue in tourism sub sector (Y). Samples were taken using a non-probabillity sampling tevhmique with a purposive sampling method. The type of research used is assosiatif research, data colectiontechniques using documentation, data analysis using multiple linier regression, The results of the multipleregression analysis are Y = -0,354X1 + 1,056X2 – 0,149X3 + 0,407X4 + e. The results of the research show that the variables number of tourist attractions and number of hotels have a partially negative effect on the Regional Original Income of the tourism sub-sector in North Lombok Regency, While the number of toursts and the number of restaurants show a partial positive effect on the Regional Ordinal Income of the Tourism sub-sector in North Lombok Regency.